THE RELATIONSHIP BETWEEN HEALTH CARE CAREERS' STIGMA TOWARDS PEOPLE WITH MENTAL DISORDERS (ODGJ) AND THEIR MOTIVATION TO BECOME A MENTAL HEALTH CARE CARE CENTER IN THE GEDONGAN PUBLIC HEALTH CENTER WORKING AREA, MOJOKERTO CITY - Imam Zainuri; Lilik Marifatul Azizah; Amar Akbar; Siti Khotijah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
https://docs.google.com/document/d/1SAsbaTPCUUSsPPboQ3fhUhjfZoD-G9bN/edit?usp=sharing&ouid=117648510977885980022&rtpof=true&sd=true